PEST Analysis Model dalam Pengembangan Potensi Wisata Pulau Benan, Kabupaten Lingga, Kepulauan Riau - Mahadiansar Mahadiansar; Aspariyana Aspariyana (Indonesian Journal of Tourism and Leisure, 2020)
The core problem of tourism sector on empowerment and natural resource development is the mapping to the potency and development strategy of tourism has not yet been maximized. This article, focus to use the PEST Model analysis to identify the growth of Benan Island as tourism destination. This research conducted through library study, and data analyzed through content analysis. The result, political, economic, social and technology factors has impacted broadly to development of Benan Island tourism in the long run. The author also purpose the alternatif model of development of priority scale tourism potential with the concept of sustainable tourism and community empowerment by involving tourism industry actors. The use of PEST Model Analysis of the tourism potential of Benan Island can also be applied to several other islands in Lingga Regency.